KNOWLEDGE - KEY FACTOR OF COMPETIVENESS OF ROAD TRANSPORT COMPANY - Sukalova, Viera; Ceniga, Pavel (Doprava a spoje, 2012)
Knowledge is important in all areas of economic activities of man; it allows create new values. Knowledge management is a part of company management that can ensure the competitiveness for every organization in current era of change and innovation; it is also a key element in building a knowledge-based economy - one of the main targets of European policy. When a transport company wants to be successful in the market, it should try to gain a competitive advantage. Road transport companies meet every day with domestic and foreign competition, so they must use and develop according to the trends in important skills and qualifications in order to maintain competition on the international and domestic market.